2020
DOI: 10.1037/ccp0000459
|View full text |Cite
|
Sign up to set email alerts
|

Attrition and adherence in smartphone-delivered interventions for mental health problems: A systematic and meta-analytic review.

Abstract: Objectives: Although the efficacy of smartphone-delivered interventions for mental health problems is emerging, randomized controlled trials (RCTs) of smartphone interventions are characterized by high rates of attrition and low adherence. High attrition and low adherence may threaten the validity of RCT findings, so a better understanding of these phenomena is needed. We examined attrition and adherence in 70 RCTs of smartphone interventions. Method: Four online databases were searched for RCTs of mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
264
4
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 389 publications
(336 citation statements)
references
References 54 publications
36
264
4
5
Order By: Relevance
“…As for the use of smartphones in mental health interventions, another meta-analysis pointed out that psychological interventions delivered via these devices reduced anxiety [ 50 ]. Nevertheless, a recent meta-analysis has showed that such interventions with smartphones were characterized by high rates of attrition and low adherence [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for the use of smartphones in mental health interventions, another meta-analysis pointed out that psychological interventions delivered via these devices reduced anxiety [ 50 ]. Nevertheless, a recent meta-analysis has showed that such interventions with smartphones were characterized by high rates of attrition and low adherence [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging empirical support also exists for the efficacy of e‐therapy interventions for EDs (Beintner, Jacobi, & Taylor, 2012; Beintner, Jacobi, & Taylor, 2014; de Zwaan et al, 2017; Loucas et al, 2014; Melioli et al, 2015), with cognitive, behavioral, and dissonance‐based prevention (e.g., Student Bodies , the Body Project ) and treatment (e.g., enhanced cognitive behavior therapy, Salut ) programs producing moderate reductions in core risk factors (Cohen's d 's range from 0.20 to 0.60) and symptoms (Cohen's d 's range from 0.40 to 1.00). However, this enthusiasm for e‐therapy has, at times, been balanced by concerns regarding high rates of attrition (Eysenbach, 2005; Linardon & Fuller‐Tyszkiewicz, 2020), and concerns that efficacy is lower for entirely automated or self‐guided e‐therapy use (Linardon et al, 2019). The notion that self‐guided e‐therapy may be best suited as a low intensity treatment within a stepped care approach has some empirical support (Karyotaki et al, 2017), but is unlikely to be satisfactory for all.…”
Section: Introductionmentioning
confidence: 99%
“…Smartphone apps have been shown to support selfmanagement and behaviour change for smoking cessation [23], cardiac rehabilitation [24], healthy lifestyle [25], diabetes [26], HIV [27], nutrition [28], mental illness [29] and youth driving [30]. In a recent metaanalysis of smartphone interventions for mental health problems, smartphone apps outperformed waitlist controls with small to medium effect sizes [31]. The effect size was greater for apps that had a theoretical basis in CBT.…”
Section: Mobile Health (Mhealth): a New Opportunity For Problem Gamblingmentioning
confidence: 99%
“…Stratified block randomisation (created by the study statistician), using block sizes of 2 and 4, will be used to randomly allocate participants. To ensure balance on potential confounders, randomisation will be stratified by ethnicity (Māori, Pacific, Other), sex and gambling symptom severity using the Gambling Symptom Assessment Scale (G-SAS): dichotomised to mild to moderate gambling symptom severity (G-SAS score 0-30) and severe to extreme gambling symptom severity (G-SAS score [31][32][33][34][35][36][37][38][39][40] to ensure a balance in these key characteristics.…”
Section: Randomizationmentioning
confidence: 99%
See 1 more Smart Citation